Hak suami isteri dalam perkahwinan Islam: Analisis menurut fiqh - Abu Bakar, Md Zawawi (Universiti Utara Malaysia, 2008)
Rights is an issue commonly surfaced in family relationships.It happens all the way through a marriage or after a divorce.This arises because a marriage is a contract(akad) between the husband and wife.Rights and responsibilities would arise through this marriage contract.A neglect for these rights and responsibilities would result in marriage crisis which often lead to divorce.Hence, this article aims at discussing the rights as stated in the Islamic marriage.Lenghty discussions on the rights of husband-wife are available in Islamic books on fiqh.The husband-wife rights is divided into two parts; first, rights in monetary forms, and second, rights in non-monetary forms.Islam has clearly prescribed the husband-wife rights and responsibilities in its attempt to preserve the household serenity.